2022
DOI: 10.3390/antiox11040753
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Cocoa-Enriched Diet on Oxidative Stress Induced by Intensive Acute Exercise in Rats

Abstract: Intensive acute exercise can induce oxidative stress, leading to muscle damage and immune function impairment. Cocoa diet could prevent this oxidative stress and its consequences on immunity. Our aim was to assess the effect of a cocoa-enriched diet on the reactive oxygen species (ROS) production by peritoneal macrophages, blood immunoglobulin (Ig) levels, leukocyte counts, and the physical performance of rats submitted to an intensive acute exercise, as well as to elucidate the involvement of cocoa fiber in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…Here, although we aimed to assess the changes immediately after exercise cessation, technical limitations meant that blood collection was actually performed 20–30 min after extenuation, which may be enough to normalize the number of circulating leukocytes and the concentration of plasma noradrenaline. On the other hand, the cocoa diet attenuated the cortisol increase, which is in line with previous studies that attribute such effect to the inhibition 11β-hydroxysteroid dehydrogenase type 1 activity by cocoa flavanoles [ 38 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, although we aimed to assess the changes immediately after exercise cessation, technical limitations meant that blood collection was actually performed 20–30 min after extenuation, which may be enough to normalize the number of circulating leukocytes and the concentration of plasma noradrenaline. On the other hand, the cocoa diet attenuated the cortisol increase, which is in line with previous studies that attribute such effect to the inhibition 11β-hydroxysteroid dehydrogenase type 1 activity by cocoa flavanoles [ 38 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, considering the exercise performance, we did not observe an improvement after 6 weeks of nutritional interventions with cocoa or cocoa plus hesperidin. This result agrees with most of the preclinical and clinical studies involving cocoa products, such as cocoa powder [ 38 , 42 , 49 ], cocoa flavanol capsules [ 37 ] or chocolate [ 36 , 50 , 51 ]. With regard to hesperidin, both preclinical [ 40 , 41 , 43 ] and clinical studies [ 35 , 39 , 52 , 53 ] have reported its ergogenic effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since the exercise duration was only six weeks, the study participants may not have acclimated to the strenuous exercise by that point, potentially leading to an exaggerated inflammatory response. A single intensive bout of exercise can cause an overproduction of ROS leading to oxidative stress and potentially tissue damage [82]. On the contrary, regular exercise, as observed in breast cancer patients, allows the body to adapt to stress, enabling it to respond swiftly and prevent or minimize the harmful effects of oxidative stress on cellular structures.…”
Section: Exercise and Its Effect On Body Composition In Cancer Survivorsmentioning
confidence: 99%
“…Although polyphenols exert their antioxidant capacity mainly through the direct neutralization of free radicals and chelating metals, such as Fe2+ and Cu+ [119,120], there are other mechanisms that have been reported, such as the stimulation of mitochondrial biogenesis through the activation of the SIRT1 and Nrf2 signaling pathways [120,121]. Nrf2, a transcription factor that regulates antioxidant responses, remains in the cytoplasm bound to the Kelch-like ECH-associated protein 1 (Keap1).…”
Section: Recent Advances In Cocoa Flavanols On Nrf2 Pathway/antioxida...mentioning
confidence: 99%